Midwifery Care for Postpartum Mothers on Ny. M P1a0 With Breast Milk Dam at Siti Kholijah Maternity Clinic, Medan Marelan, 2018 - Devi Susana Pinem; Ernita Ruslaini Chaniago Caniago; Hilda Yati; Juli Antika (Institute of Computer Science (IOCS), 2018)
The IDHS data recorded that the maternal mortality rate in Indonesia in 2007 was 228/100,000 live births and about 60% of deaths occurred during the puerperium. The direct causes of maternal death in Indonesia are bleeding (30%), infection (12%), eclampsia (11%), prolonged labor (5%), abortion (5%). The second largest percentage is infection. Infections in the mother occur during pregnancy such as urinary tract infections, during childbirth such as intrauterine infections, and during the puerperium such as mastitis and breast abscesses that are preceded by the presence of dams in the milk ducts. Case Study Objectives: Able to carry out midwifery care for postpartum mothers on Mrs. M P1A0 with a breast milk duct dam at the Siti Kholijah Maternity Clinic with 7 steps Varney. Types of Case Studies: The method used in this case study is descriptive. The case study was conducted at the Raskita Sendang Rejo clinic on Ny. M P1A0 aged 26 years with a breast duct dam, using the format of midwifery care for postpartum mothers according to Varney's midwifery management and carried out on March 16, March 18, 2015. Data collection techniques were through interviews, observations, physical examinations, documentation studies and literature studies. Case Study Results: After 3 days of antalgin therapy 500 mg orally 3x1 paracetamol 2 x1 breast care, and breastfeeding the baby properly and correctly, the results showed that the problem could be resolved, there was no maternal anxiety, the mother's fever dropped, pain and swelling disappeared, lactation became smooth, the mother was able to breastfeed her baby smoothly and the dam of the milk duct was resolved. The conclusion from the results of writing this scientific paper is that breast milk duct dams can be overcome with appropriate treatment, namely 500 mg antalgin therapy and paracetamol 2x 1 orally, breast care, and breastfeeding the baby properly so that breast milk can come out smoothly and the breast milk duct dam has resolved..